Let "r","s" and "t" be the roots of x 3 + 4 x 2 + 3 x + 2 = 0 . Find ( 1 / s t ) + ( 1 / r t ) + ( 1 / r s ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Please provide a complete solution. @Paul Ryan Longhas
Log in to reply
In the equation x^3 + ax^2 + bx + c = 0. r + s + t = -a and rst = -c, so in the equation x^{3} + 4x^{2} + 3x + 2 = 0 ----> r + s + t = -4 and rst = -2.
He just used Vieta's formulas for a cubic polynomial. The general form can be seen here
He used the integral root theorem....
Log in to reply
Not quite. Note that the cubic polynomial equation in the problem has no integral roots. He just used Vieta's formulas, nothing else.
Given the roots of p ( x ) = x 3 + 4 x 2 + 3 x + 2 are r, s and t, find s t 1 + r t 1 + r s 1 .
Note that the desired value involves the reciprocals of p(x)'s roots.
By reversing the order of p(x)'s coefficient 1 , we get a new polynomial, q ( x ) = 2 x 3 + 3 x 2 + 4 x + 1 with reciprocal roots, r 1 , s 1 and t 1 .
Therefore, s t 1 + r t 1 + r s 1 = 4 / 2 = 2
1 See Chapter 4, Transforming Polynomials, Example 4.1 of Khan, Adeel. "A Few Elementary Properties of Polynomials." (2006)
x^3 + 4x^2 +3x + 2 = 0
Vieta's formulas
r + s + t = -b/a = -(4)/(1) = -4
rs + rt + st = c/a = (3)/(1) = 3
r s t = -d/a = -(2)/(1) = -2
1/st + 1/rt + 1/rs = (r + s + t) / (r s t) = (-4) / (-2) = 2
s t 1 + r t 1 + r s 1 = r s t r + s + t From Vieta,s formulas,we know that r + s + t = − 4 . r s t = − 2 so : r s t r + s + t = − 2 − 4 = 2
Problem Loading...
Note Loading...
Set Loading...
since r + s + t = -4 and rst = -2. And (1/st) + (1/rt) + (1/rs)= (r+s+t)/rst = -4/-2 = 2